2021
DOI: 10.1002/cpz1.250
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase Assays

Abstract: Other/unknown C1D, MGMT, PTMA b , TDP1a These methyltransferases form adducts with RNA only.b PTMA was shown to form adducts with RNA only. BASIC PROTOCOL 1 ASSAY OF TOPOISOMERASE I ACTIVITYA principal reaction of topoisomerase I is the relaxation of supercoiled DNA, which is readily distinguished from relaxed (not supercoiled) DNA based on electrophoretic mobility. Plasmid DNA isolated from most natural sources is negatively supercoiled, and any Nitiss et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 118 publications
1
19
0
Order By: Relevance
“…Given the heterogeneity of the non-enzymatic DPCs induced by FA, the repair of those DPCs remains only partially known. Understanding the protein identity of as well as chromosome regions, DNA transactions and DNA structures involved in the DPCs is therefore important to study 34, 35 non-enzymatic DPC repair. A major challenge to profiling non-enzymatic DPCs is their purification.…”
Section: Resultsmentioning
confidence: 99%
“…Given the heterogeneity of the non-enzymatic DPCs induced by FA, the repair of those DPCs remains only partially known. Understanding the protein identity of as well as chromosome regions, DNA transactions and DNA structures involved in the DPCs is therefore important to study 34, 35 non-enzymatic DPC repair. A major challenge to profiling non-enzymatic DPCs is their purification.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the accumulation of trapped TOP2 using the ICE bioassay (Anand et al, 2018;Nitiss et al, 2021)by transiently transfecting RH30 cells, a pediatric rhabdomyosarcoma cell line with siRNA against MRE11 or non-targeting siRNA (Figure 1A) followed by treatment with etoposide at various concentrations (2, 10, 50 μM) for 2 h. In accord with findings that MRN complex is involved in the release of the TOP2-like protein Spo11 from DNA in S. cerevisiae and that Rad32 (Mre11) plays a role in Top2 removal in S. pombe (Hartsuiker et al, 2009), we found that both hTOP2α and βcc levels in MRE11-deficient cells were distinctly higher than those in WT cells (transfected with control siRNA) treated with 10 μM etoposide (Figure 1B). However, for etoposide treatments at low concentration (2 μM) or high concentration (50 μM), we failed to observe a significant difference in TOP2α or TOP2βcc levels between MRE11 knockdown cells and WT cells.…”
Section: Resultsmentioning
confidence: 99%
“…Other approaches for detecting elevated levels of TOP2ccs and based on similar biophysical principles have been described, including the TARDIS assay (Willmore et al, 1998) and the RADAR assay (Kiianitsa and Maizels, 2013). A detailed description of some of these assays along with detailed methodological considerations has recently been presented (Nitiss et al, 2021). The ICE assay has been previously used to demonstrate the importance of SUMO, ubiquitin and poly (ADP-ribose) modification of topoisomerases in repairing the enzyme-induced damage (Sun , 2020a;Sun et al, 2021;Sun et al, 2022b), potential roles of p53 in the regulation of repair functions for topoisomeraseinduced damage (Menendez et al, 2022), and the identification of novel repair activities (JLN, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The DUST assay ( 8 ) is an extension of the RADAR assay developed by Maizels and colleagues for detecting proteins covalently bound to DNA ( 49 , 50 ). The DUST assay is an extension of the assay that also allows detection of posttranslational modifications on proteins covalently bound to DNA by using antibodies directed against the modifications.…”
Section: Methodsmentioning
confidence: 99%